The Role of The Indonesian Language in Negotiations between Msme Actors and Consumers in Galis District - Dinda Retno Damayanti; Farah Fahryzah; Moh. Anil Alfa Marom; Bima Kurniawan (Educational Journal, 2026)
This study aims to describe the role of the Indonesian language in the negotiation process between actors of Micro, Small, and Medium Enterprises (MSMEs) and consumers in Galis District, Bangkalan Regency. Language is an essential element of economic activity because it functions as a medium for conveying information, offering products, and conducting bargaining between sellers and buyers. This study used a descriptive qualitative approach, with data collected through semi-structured interviews and direct observation of MSME actors at Galis Market. The results show that MSME actors in Galis District use two languages interchangeably, namely Madurese and Indonesian, selected according to the background and character of the consumer. Indonesian is used mainly when interacting with consumers from outside the region or in more formal situations, while Madurese is used to build emotional closeness with local consumers. Persuasive language strategies, such as complimenting the product, emphasizing price advantages, and using a friendly and polite tone, have been shown to increase the effectiveness of negotiation. However, limited Indonesian language proficiency among some business actors and dialectal differences constitute obstacles that hinder effective communication. This study concludes that good command of Indonesian, combined with proficiency in the local language, contributes significantly to negotiation success, consumer trust, and the sustainability of MSME businesses in Galis District.